Knowledge, Perceived Competence, and Behaviors Relative to Traumatic Brain Injury Among a Sample of Domestic Violence Emergency Shelter Advocates in a New England State - Campbell, Julia K. (Violence against women, 2024)
This cross-sectional study describes knowledge, perceived competence, and behaviors relative to intimate partner violence (IPV)-related brain injury (BI) among staff in residential domestic violence shelter programs across a New England state. A 23-item questionnaire was administered to registrants of an online IPV-related BI training series. Within this sample, knowledge about IPV-related BI was high, but relative to providing screening, accommodations, and specialized referrals to survivors with BI, perceived competence was low, and behaviors were infrequent. IPV shelter agencies should facilitate IPV-related BI training programs for staff and prioritize developing and implementing BI screening, accommodation, and referral policies and procedures.